Early start of DOAC after ischemic stroke: Risk of intracranial hemorrhage and recurrent events. (1st November 2016) - Seiffge, David J.; Traenka, Christopher; Polymeris, Alexandros; Hert, Lisa; Peters, Nils; Lyrer, Philippe; Engelter, Stefan T.; Bonati, Leo H.; De Marchis, Gian Marco
Abstract : Objective: In patients with recent acute ischemic stroke (AIS) and atrial fibrillation, we assessed the starting time of direct, non–vitamin K antagonist oral anticoagulants (DOACs) for secondary prevention, the rate of intracranial hemorrhage (ICH), and recurrent ischemic events during follow-up. Methods: We included consecutive patients with nonvalvular atrial fibrillation admitted to our hospital for AIS or TIA (index event) who received secondary prophylaxis with DOAC or vitamin K antagonists (VKAs). Follow-up was at least 3 months. In the primary analysis, we compared rates of ICH and recurrent ischemic events (AIS or TIA) between patients with early (⩽7 days since event; DOACearly ) and those with late (>7 days, DOAClate ) start of DOAC. Results: Two hundred four patients were included (median age 79 years, 89% AIS) and total follow-up time was 78.25 patient-years. One hundred fifty-five patients received DOAC with a median delay of 5 days after the index event (interquartile range 3–11) and 49 received VKA. DOAC was started early in 100 patients (65%). We observed one ICH (1.3%/y) and 6 recurrent AIS (7.7%/y). The ICH occurred in a patient taking VKA. No significant difference in the rate of recurrent AIS between DOACearly (5.1%/y) and DOAClate (9.3%/y, p = 0.53) was observed. Conclusions: Even if DOACs are often started early after an index event, the risk of ICH appears to be low. Among all patients receiving anticoagulation, the rate of recurrent events was 6 times higher than the rate of ICH.